Active layer thermal regime varies across landforms in a subarctic wetland - Gillian Muir; Glen S. Brown; Kapillesh Balasubramaniam; Baoxin Hu (FACETS)
The fine-scale controls of active layer dynamics remain poorly understood, particularly at the southern boundary of continuous permafrost. We examined how environmental conditions associated with upland tundra heath, open graminoid fen, and palsa/peat plateau landforms affected active layer thermal regime (timing, magnitude, and rate of thaw) in a subarctic peatland in the Hudson Bay Lowlands, Canada. A significant increase in active layer thaw depth was evident between 2012 and 2024. Within-season thaw patterns differed among landforms, with tundra heath exhibiting the highest thaw rates and soil temperatures, succeeded by fen and palsa. Air temperature mediated by soil properties, topography, and vegetation affected thaw patterns. The increased thermal conductivity of gravel/sandy tundra heath soils exerted a more pronounced influence on thaw patterns relative to fens and palsas, both of which had a thicker organic layer. Near-surface soil moisture was the lowest in tundra, followed by palsas, and fens. Increased soil moisture impeded active layer thaw, likely due to a combination of soil surface evaporation and meltwater percolation. These findings elucidate the relationship between the biophysical properties of landform features and climate, revealing their role in influencing active layer thaw patterns in a subarctic ecosystem.